FACTORS ASSOCIATED WITH CARBON TAX AWARENESS: A SYSTEMATIC REVIEW: Factors associated with carbon tax awareness: A Systematic Review - Ahmed Bagubair, Ahmed Awadh; Abd Ghani, Norfarihah; Ahmad Daud, Arfizah; Bin Baharuddin, Muhammad Zul Aizzat; Dr Rahmat Dapari; Mansor, Zawiah; Che Dom, Nazri; Hassan, Mohd Rohaizat; Syed Abdul Rahim, Syed Sharizman (Malaysian Journal of Public Health Medicine, 2024)
Carbon dioxide is the primary greenhouse gas responsible for approximately three-quarters of the world’s gas emissions. Carbon dioxide (CO2) is an important heat-trapping gas, or greenhouse gas that comes from the extraction and burning of fossil fuels. Its presence in the atmosphere warms the planet, but the rising concentration of greenhouse gases has led to climate change due to hotter temperatures across the globe. Carbon tax is defined as a fee imposed on the burning of carbon-based fuels, such as coal, oil, and gas, which aims to reduce greenhouse gasses. Thus, this study aimed to evaluate the factors associated with carbon tax awareness among the general population. This systematic review aimed to systematically evaluate factors associated with carbon tax awareness among the general population. A systematic search was conducted in Scopus and ScienceDirect. This review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The literature search was conducted from 1st November until 1st December 2022 using Scopus and ScienceDirect databases. The following keywords were used to search for related articles: “carbon tax policy” AND “awareness” AND “factor” OR “factor associated”. All retrieved articles were imported into EndNote20. A total of two studies met the inclusion and exclusion criteria, with one eligible article from Taiwan and 1 from Canada. The analysed articles were published between 2020 and 2022. The identified associated factors of carbon tax awareness, namely trust in the federal government, climate change concerns, environmental concerns, education, health consciousness, and age, can be used as a guide for designing evidence-based measures and policies that address these concerns.